THE CONCEPTS: INTERACTIVE LEAR NING FOR ADULT LEARNERS - Sysoieva, S. (Continuing Professional Education: Theory and Practice, 2019)
The paper deals with the interactive technologies in adults education: the definitions of “interactive learning”, “interactive technology” for adult learners, the interactivity for the adult distance learning systems, efficiency criteria and stages of the adults interactive technologies development